The clinical significance of insulin-like growth factor-1 and cystatin C in predicting the risk of developing complications of chemoresistant pulmonary tuberculosis in patients undergoing palliative treatment - Raznatovska, O. M.; Khudiakov, H. V. (Zaporozhye Medical Journal, 2019)
In contemporaryUkraine, the urgency of pulmonary chemoresistant tuberculosis (CRTB) problem is evident as it is the cause of severe clinical condition, subjective and functional disorders causing disease-specific distress in patients. This disease is a common cause of palliative treatment (PT) for patients requiring professional medical care. The goal of PT for patients with pulmonary CRTB should be to improve the quality of life (QoL) by priority of stress reduction which occurred as a result of the underlying disease complications. The purpose – to evaluate the clinical relevance of insulin-like growth factor-1 (IGF-1) and cystatin C for predicting the risk of pulmonary CRTB complications among patients in PT. Materials and methods. The study enrolled 81 patients with pulmonary CRTB who were treated in a Communal Institution “Zaporizhzhia Regional Hospital” and a Specialized Tuberculosis Hospital at the State Institution “Sophia penal colony (№ 55)” of the Ministry of Justice of Ukraine in the Zaporizhzhia Region. All patients (100 %) were male. The main group consisted of 52 patients receiving PT, the average age was 35.0 (28.0; 51.7) years. The control group included 29 patients receiving antimycobacterial therapy (AMBT) by category 4 according to the drug resistance profile. Study groups were age- and gender-matched. Serum levels of cystatin C and IGF-1 were measured by an enzyme-linked immunosorbent assay (ELISA) with an immunoassay reader “Sirio S” using the kit “Human Cystatin C ELISA BioVendor Research and Diagnostic Products” (ng/ml; Czech Republic) and “Human IGF-1 ELISA” (ng/ml, Germany), respectively. The measurements were performed in the Immuno-enzymatic Laboratory of the Training Medical Laboratory Center of ZSMU. Results. Among the patients with pulmonary CRTB who received the PT, high inflammatory process activity, pronounced decrease in the quality of life and underweight as well as decrease in serum concentrations of cystatin C and IGF-1 were determined 1 month after the beginning of inpatient treatment. It was found that palliative patients who died the following month after being treated in the hospital compared to those who continued the PT, showed 1,6 times increased serum level of TNF-α, a tendency to further decrease in both cystatin C and IGF-1 serum levels to 1572.8 (911.6; 2278.8) ng/ml and 5.0 (2.1; 6.4) ng/ml, respectively. The decrease in serum concentrations of these indicators was significantly correlated with all the studied parameters in palliative patients with pulmonary CRTB both, who continued the treatment and who died. At the same time, in palliative patients who died, a decrease in serum levels of cystatin C and IGF-1 was strongly correlated with a decrease in the quality of life: (r = 0.927; P = 0.01) and (r = 0.820; P = 0.01), respectively. The average body mass index (BMI) was 18.0 (15.8; 20.1) kg/m2 in these patients indicating the prevalence of underweight among them, and the high direct correlation between BMI and low serum concentrations of IGF-1 (r = 0.986; P = 0.01) and cystatin C (r = 0.728; P = 0.05) was indicative of a close relationship between cachexia and a decrease in the levels of anabolic processes impairment biochemical marker (IGF-1) and early marker of heart failure (cystatin C). Autopsy-identified causes of these patients death were heart failure and cachexia on the background of a specific process. A direct correlation was also found between decreased serum concentrations of IGF-1 and cystatin C in palliative patients with pulmonary CRTB both, who continued the treatment and those who died: (r = 0.901; P = 0.01) and (r = 0.732; P = 0.05), respectively. Conclusions. Determination of IGF-1 and cystatin C serum concentrations has a great clinical significance in predicting the risk of complications such as heart failure and cachexia in patients with pulmonary CRTB receiving palliative treatment.